A numerical study of the Timoshenko model with dissipative mechanisms (Selecciones Matemáticas, 2020)
In this work we gather works from the literature that present the qualitative study via linear semigroups to the Timoshenko Beams System with dissipative mechanisms. Such problems do not have an analytical solution, but with the use of the exponentials theory of non-limited operators and Functional Analysis tools, it is possible to perform the asymptotic analysis for the models presented. Therefore, the objective of the work is accomplish a numerical analysis, using finite difference methods. We show that the qualitative results, proven by the semigroup theory, are verified for beam with concrete material and aluminum material.
Keywords: Exponential Stability; Dissipative Mechanisms; Finite Differences